การศึกษาสภาพและปัญหาการบริหารงานการเงินและบัญชีของสถานศึกษา สังกัดกองการศึกษาอาชีพ กรมอาชีวศึกษา - สุณี แก้วเกาะ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research was to stdy the state and problems of financial and accounting administration in colleges under the industrial and community education, department of vocational education. The study sample consisted of 65 directors, 65 assistant directors for administrative affairs, 65 head of financial sections, and 65 head of accounting sections. The instruments used were questionnaire. Statistics used to analyze collected data were frequency and percentage. The study revealed that the state of financial and accounting administration were : college had financial and accounting planned, form planning committees; operation plan was done for spending money; that the method used in operation planned was to collected data, problems and needs of the college; form meeting and discussion; collected rules, regulation concerning financial and accounting were provided for using; a internal financial and accounting audit committees; head of financial sections was filing financial and accounting documents; a committees keep college’s money; a systematizing control of spending money according to the operation plan; evaluation was done by assistant directors for administrative affairs when the end of project for financial and accounting planning. The problems revealed in the study were : lack of enough money; lack of internal supervision concerning financial and accounting regulations; lack of personnel who had the knowledge understanding and skill in constructing the evaluation instrument.